The Effect of NPL, LDR, and Bopo on Company Value (PBV) Through Roa and Company Value (PBV) on Investment Decisions (PER) - Mustikaweni, Riezkiani; Tesniwati, Rini; Kustamtinah, Lisna; Dahliawati, Anne (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
The success of bank companies in increasing profits can be seen from the effectiveness and efficiency of banks in using their assets optimally. The aim of this research is to determine and analyze the influence of Credit Risk, Liquidity and Efficiency Level on Company Value with Profitability as an Intervening Variable and the influence of Company Value on investment decisions in Banking Companies listed on the Indonesia Stock Exchange that have met the criteria for the 2016-2022 period. The sampling method used in this research is the purposive sampling method. The sample obtained was 12 banking companies from 41 populations. The research uses secondary data obtained from annual reports on each company's website. The data analysis technique used in this research is path analysis using AMOS 23 software. The results of this research show that credit risk and the level of efficiency have a negative effect on profitability. Liquidity has no effect on profitability. Credit risk, liquidity and efficiency levels have a negative and significant effect on company value. Profitability has no effect on company value. Profitability mediates the influence of credit risk, liquidity, and efficiency level on company value. Company value has a positive effect on investment decisions